Sleep and Pain in Mid- to Late-Life: An Exploration of Day-to-Day Pain Inconsistency. Issue 2 (15th March 2018) - Ravyts, Scott G.; Dzierzewski, Joseph M.; Grah, Stephanie C.; Buman, Matthew P.; Aiken-Morgan, Adrienne T.; Giacobb, Peter R.; Roberts, Beverly L.; Marsiske, Michael; McCrae, Christina S.
ABSTRACT: Objectives : This study examined how different quantifications of pain (average vs. day-to-day inconsistency) are related to sleep in older adults beyond known predictors. Methods : Baseline measures from the Active Adult Mentoring Project were used for secondary analyses. Participants included 82 adults in mid- to late-life. Depression was assessed with the BDI-II. Pain intensity was assessed over seven days on a 11-point Likert-scale, while sleep efficiency (SE), total sleep time (TST), and total wake time (TWT) were assessed using a self-report diary. Results : Regression analyses revealed that pain inconsistency was associated with both SE and TWT and accounted for significant variance over age, gender, and depression. In contrast, average pain was not associated with SE, TST, or TWT. Conclusions : The findings indicate that pain inconsistency may be a more meaningful predictor of sleep disturbance than average pain level, suggesting that one's ability to regulate pain may be related to one's ability to engage in optimal sleep in mid- to late-life. Clinical Implications : Pain inconsistency appears to contribute more to sleep disturbance than average pain. Pain inconsistency in late-life warrants greater attention and may be an area of clinical intervention through activity-pacing or coping skills training.